دور حماية حقوق الملكية الفكرية في تحسين جاذبية الدولة للاستثمارات - عرض تجارب دولية – (مجلة الواحات للبحوث والدراسات, 2015)
Investments are considered essential to the growth of the national economy because of this importance, became intensified competition between countries for a growing share of these investments, which help to develop their economies and facilitating integration in the global economy. However, we must emphasize that the attractiveness of local and foreign investment depend on the existence of many determinants essential for host countries to ensure competition in this area, among others the protection of intellectual property rights, which is the one of the main conditions. Rights to patents, copyrights, trademarks, geographical indications and trade secrets; a third of the value of investments of large companies in the world. While the lack of effective protection of this element can not attract quality foreign investments in the national economy, which is seen as a means of technology transfer and knowledge. Indeed, many countries have focused on the issue of protection of intellectual property rights while others have contributed to the international effort to protect it.